THE DEVELOPMENT OF EARLY CHILDHOOD TEACHER QUALITIES IN SUPPORTING CHILDREN’S GROWTH TOWARD THEIR FULL POTENTIAL BASED ON CONTEMPLATIVE EDUCATION APPROACH - Siripat, Aparat; Pongpakatien, Jirattakarn; Sumamal, Arisa (Journal of Educational Review Faculty of Education in MCU, 2025)
This research utilized an action research approach with the objectives of (1) developing a process to cultivate early childhood teacher qualities that support children’s growth toward their full potential based on a contemplative education approach, and (2) examining the outcomes of this process on the development of early childhood teacher qualities. Qualitative data were collected through various research instruments, including participatory observation during the process, pre- and post-process interview records, focus group discussion notes, and reflective journals from participants. The data were analyzed using qualitative methods, particularly inductive analysis, to synthesize information from multiple sources and gain a deeper understanding of the process outcomes in terms of teachers’ knowledge, attitudes, and inner dimensions. The participants in this study consisted of 12 early childhood teachers from a private school in Bangkok who voluntarily joined the program. The group included seven homeroom teachers from kindergarten levels 1 to 3 and five assistant teachers. Participant selection was based on teachers’ willingness and readiness to engage fully in all activities throughout the process. The findings revealed that 1) The developed process which aim to enhance six key teacher qualities: (1) the ability to create a secure attachment with students, (2) belief and faith in human potential, (3) appreciation of individuality and uniqueness, (4) self-awareness, (5) recognition of interconnectedness with all things, and (6) kindness and the ability to be a supportive ally to students are to be conducted over four sessions totaling 10 days. The process includes objectives, principles, preparatory steps, process design, and evaluation. The process emphasizes fostering inner awareness and understanding of essential concepts such as Executive Function (EF) skills, Multiple Intelligences theory, and authentic education and 2) Teachers participating in the process demonstrated learning aligned with the objectives, with particularly notable development in self-awareness and the ability to create secure attachments, which were the most evident improvements. Recommendations for implementing the process should focus on maintaining core principles, including self-awareness, while adapting to the context of each school. It is essential to create a safe learning environment, support the continuous inner development of teachers, and establish a monitoring system that captures behavioral changes and real-life impacts to ensure ongoing and sustainable development.